Stigma dan diskriminasi terhadap pesakit HIV oleh kakitangan paramedik di Pejabat Kesihatan Daerah Gombak - Mohd Razif, Sidek (2020)
Stigma and discrimination against People Living with HIV (PLHIV) is still prevalent today. This study was conducted to determine whether knowledge influences stigma and discrimination. In addition, this study was also conducted to determine whether negative attitude influences stigma and discrimination. The quantitative method was used in this study involving 152 respondents comprising 31 Assistant Medical Officers (U29) and 121 Staff Nurses (U29) working at the Gombak District Health Office. Questionnaires were distributed to respondents. The selection of respondents is a simple random sampling method. The results of this study indicate that there is a significant relationship between poor knowledge and attitudes that creates stigma and discrimination against PLHIV. Employees with high knowledge and adverse attitudes toward PLHIV have stigmatized and discriminated against them. This study has led to a slightly different finding that requires more comprehensive studies in the future and a better approach should be taken to look at the curriculum involved in training activities for health staff.